Ethnic Inequality and Economic Growth: Evidence from Harmonized Satellite Data - Klaus Gründler; Andreas Link (Center for Economic Studies and ifo Institute (CESifo), 2024)
Inequality between ethnic groups has been shown to be negatively related to GDP, but research on its effect on contemporary economic growth is limited by the availability of comparable data. We compile a novel and comprehensive dataset of harmonized Gini indices on ethnic inequality for countries and sub-national units between 1992 and 2013. Our approach exploits differentials in nighttime lights (NTL) across ethnic homelands, using new techniques to harmonize NTL series across geographic regions and years to address concerns about spatial and temporal incomparability of satellite photographs. Our new data shows that ethnic inequality is widespread across countries but has decreased over time. Exploiting the artificiality of sub-national borders in an instrumental variable setting, we provide evidence that income inequality across ethnic groups reduces contemporary economic growth. The negative effect of ethnic inequality is caused by increasing conflict and decreasing public goods provision.
Keywords: O10; O15; O43; 330; ethnic inequality; economic development; regional data; nighttime lights; satellite photographs; calibration; ethnic groups; conflict; public goods provision